2017
DOI: 10.11637/kjpa.2017.30.2.39
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Absorbable and Nonabsorbable Sutures for Open Repair of Achilles Tendon Rupture: A Pilot Study

Abstract: : This pilot study was performed to compare the functional and clinical results including complications after surgery in the open repair of Achilles tendon rupture with regard to the type of suture material. A consecutive series of twenty patients with acute Achilles tendon rupture who underwent open repair were enrolled in this pilot study. The patients were divided equally into 2 groups according to suture type. In the nonabsorbable suture group, No. 2 braided nonabsorbable polyethylene terephthalate sutures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…In spite of such differences in scar tissue formation between distinct suture materials, no significant difference was found between the two groups in terms of AOFAS ankle-hindfoot score or postoperative complications. Similarly, previous studies have shown that absorbable and nonabsorbable suture materials have similar postoperative functional outcomes, although more postoperative complications have been observed with nonabsorbable sutures [ 5 , 10 , 11 ]. Nevertheless, it should not be overlooked that the tendons appearing in MRI in this study were still in the process of healing, as all of them were taken approximately 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In spite of such differences in scar tissue formation between distinct suture materials, no significant difference was found between the two groups in terms of AOFAS ankle-hindfoot score or postoperative complications. Similarly, previous studies have shown that absorbable and nonabsorbable suture materials have similar postoperative functional outcomes, although more postoperative complications have been observed with nonabsorbable sutures [ 5 , 10 , 11 ]. Nevertheless, it should not be overlooked that the tendons appearing in MRI in this study were still in the process of healing, as all of them were taken approximately 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 58%
“…Considering these issues, it is known that absorbable suture material not only has sufficient holding capacity and strength, but also results in similar postoperative functional outcomes to nonabsorbable suture material [ 8 , 9 ]. Moreover, fewer postoperative complications are observed with absorbable sutures [ 10 , 11 ]. However, to our knowledge, little is known about whether the morphology of the repaired Achilles tendon varies according to suture material because it is not apparent on routinely obtained plain radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of current study were this was a retrospective study and had heterogeneity of the study population. The use of nylon 2-0 in current study is not a common suture material for repair of Achilles tendon and needs more studies to justify it [23].…”
Section: Discussionmentioning
confidence: 97%
“…Suture sizes 2-0 and 3-0 are commonly used for human flexor tendon repairs, and these sizes of barbed sutures were used in previous cadaver and animal in vivo repair studies. 11,18,19,[23][24][25] Manufacturers report that the mechanical properties of barbed sutures are similar to those of non-barbed sutures of one size smaller. 26 Therefore, size 2-0 (non-barbed and barbed) and 3-0 (barbed) sutures were examined in this study.…”
Section: Methodsmentioning
confidence: 99%